(untitled) (International Educators Conference, 2025)
The article presents a methodology for developing conversation, which is effective in increasing the ability to master a foreign language in educational institutions, and its description. Exercises and recommendations for this method are given to accelerate language learning. Instructions for their use in the lesson are given.